Development of Extragenital Lichen Sclerosus in Malignant Melanoma Patients Treated With Ipilimumab in Combination With Nivolumab - Seyed Jafari, S. Morteza; Feldmeyer, Laurence; Hunger, Robert E. (Frontiers in Oncology, 2020)
The immune checkpoint inhibitors opened a new era for the treatment of melanoma. Nowadays, combined immune checkpoint inhibitors are administered to provide additive or synergistic effects on anti-melanoma immunity. The use of these drugs comes with serious adverse events related to excessive immune activation. Here, we present development of extragenital lichen sclerosus in a patient with metastatic malignant melanoma, during the combined therapy with checkpoint inhibitors.